(3McGjI GdSjGSI (B/s - (3YHOGddg(B, (3YHOGdNGdb(B.s ((3CHhXHj (B- (3OhdI GdGeGQGJ GdYQHjI GdeJMOI(B:s (3eQcR GdGeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjI(B,s, 2022)
(3eY Cf McGjI GdSjGSI oehpZdlI aj GdpbOe, heJOGnhdI Ydi fWGb hGSY, hjYQagG GdbGUj hGdOGfj; aEnqfgG JJLnqOO HJZoqjQ GdCMhGd hGdOhd hGdMcheGJ, hJJWnqhQ eY GdRef, hJeoqQ HeQGMd eJQGHWI(B. (3hJCJj GdSjGSI aj pUnjmZ, HSjWI heYnqbOI, haQOjI hLeGYjI, heMdjI hYGdejI, hYfOeG JNhV GdSjGSI eYGQc, hJcSH LhdGJ hJfgRe eQGJ, hJJbnqOe NWhI hJJQGLY NWhGJ, hJJhnqSY CMjGkfG hJfceT CMjGkfG CNQi; aEf dcd Pdc McGjI; Hd McGjGJ JedC GdcJH, hJajV HgG GdeDnqdaGJ GdbOjeI hGdMOjKI(B. (3hdcd YUQ McGjJg GdNGUI eY GdSjGSI, hdcd SjGSj bUJg, hdcd eLJeY ehbYg, hdcd eacQ WQjbJg aj SQO GdMcGjI, GdJj jecf Cf JZhU aj GdJaGUjd GdYejbI hGdTGFcI, Ch JXd Ydi GdSWM JdGeS GdTcd Ohf GdeVehf(B.s
Keywords: (3GdYdhe GdSjGSjIs; (3GdSjGSjIs; (3GdacQ GdSjGSjs; (3GdfXe GdSjGSjIs